GOAL-DIRECTED FLUID THERAPY IN MAJOR THORACO-ABDOMINAL SURGERY - Djukanovic, Marija; Palibrk, Ivan; Stojakov, Dejan (Medicinski podmladak, 2024)
Goal-directed fluid therapy (GDFT) in the thoracic-abdominal surgery has proven to be very challenging for many years. Minimal-invasive hemodynamic monitoring has become the standard at the Enhanced recovery after surgery – ERAS protocols. Additionally, established protocols in anesthetic management for major surgery recommend goal-directed fluid therapy. However, the use of GDFT remains controversial in certain surgical operations due to specific conditions (pneumoperitoneum or caponothorax in endoscopic procedures, open chest, protective mechanical ventilation in one lung ventilation). The modern advanced hemodynamic monitoring is less invasive and provides numerous hemodynamic variables for simple interpretation. Numerous studies have demonstrated the use of goal-directed therapy in intraoperative fluid replacement and its beneficial effects on lower postoperative morbidity and treatment costs. Using available literature performed different medical search strategies, the present review shows potential solutions to overcome the application limitations of advanced minimally invasive hemodynamic monitoring during toraco-abdominal surgery. With these options, hemodynamic monitoring will be used extensively to reduce postoperative complications and mortality. The customized strategy for patients, surgical intervention, and intraoperative losses is essential for both monitoring decision-making and achieving previously given goals for intraoperative fluid balance. This strategy has a direct impact on improving postoperative outcomes following surgery.